OPTIMIZATION OF BLUE FINANCE IN SUPPORTING MARINE SECTOR SUSTAINABILITY - Desi Efna; Muammar Khaddafi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This article explores the potential for optimizing blue finance in supporting the sustainability of the marine sector, particularly through analysis of financial management in the fishing industry. Through a mixed methodology approach, this research identifies key challenges such as lack of awareness, difficulties in measuring environmental impacts, and limitations of supportive policies. The research results show that blue finance can be significant in improving operational and ecological sustainability in the fishing industry if supported by adequate education, clear impact measurement standards, and inclusive policy reform. This research suggests that closer collaboration between government, the fishing industry and financial institutions is needed to overcome these obstacles and maximize the benefits of blue finance. This will help strengthen economic sustainability while protecting marine ecosystems